Marriage Dispensation Dysfunction and Its Implementation in Efforts to Prevent Child Marriage - Jasmin, Suriah Pebriyani; Asdar, Asdar; Mubarak, Fathul (Institut Agama Islam Negeri Kendari, 2024)
This study aims to describe the existence and role of marriage dipensation in preventing early marriage which has an impact on the problem of maternal mortality. This research is legal research using a statutory approach and a case approach, so that it can be said to be socio-legal research. The results of this study outline that: first, early marriage can be carried out if it obtains legality from 2 (two) authorized institutions, namely the religious court and the Office for the Empowerment and Protection of Women and Children (DP3A); second, marriage dispensation has an important role in marriage administration (recording), so that if you do not have marriage dispensation, administratively the marriage is not recognized by the state; third, marriage dispensation can be given to young women provided there is medical evidence from an expert doctor; fourth, that the community considers that the legality of a marriage is secondary and only administrative. Therefore, marriage dispensation should function and become a solution as a preventive measure to prevent early marriage which has an impact on the death of mothers and/or children.